Heal yourself with medical hypnosis [compact disc, unabridged] : the most immediate way to use your mind-body connection - Weil, Andrew (Sounds True, 2005)
Mind-body specialists Weil and Gurgevich explain the value of hypnosis in overcoming a variety of conditions, including insomnia, asthma, skin conditions, and immune function. Gurgevich explores four techniques for self-inducing trance states and leads a complete hypnosis healing session suitable for any condition.